Efektivitas Pemberian Minuman Bunga Telang (Clitorea Ternatea) untuk Mengurangi Nyeri Menstruasi pada Remaja Puteri - Kenhapsari, Devinta Widya; Wijayanti, Krisdiana; Djamil, Masrifan (Journal of Telenursing (JOTING), 2024)
This study aims to make a formula for butterfly pea flower drink and analyze the effectiveness of giving butterfly pea flower drink (clitorea ternatea) to reduce menstrual pain in adolescent girls. This research uses a true experiment design with a pretest - posttest design. The results there was a significant difference between the intervention group and the control group, namely a decrease in the dysmenorrhea pain level with a p-value of <0,05 in the intervention group with given at a dose of 50 mg/Kg BW although at a second dose of 25 mg/Kg BW. From the statistical results, it was found that the greatest reduction in pain was in the intervention group with a dose of 50 mg/kb BW, p-value >0.05. The conclusion, Giving butterfly pea flower drink (clitorea ternatea) at a dose of 50 mg/kg BW and a dose of 25 mg/kg BW is effective as an effort to reduce menstrual pain in adolescent girls. Keywords : Butterfly pea flower (clitorea ternatea), Menstrual Pain (Dysmenorrhea), Adolescent Girls.